Impact of Transformational Leadership on Organizational Citizenship Behavior - Thohirah, Shahidan (2011)
The main objective of this study is to determine the relationship between transformational leadership behavior and its dimensions and organizational citizenship behavior (OCB). The dimensions of transformational leadership behavior are idealized influence, inspirational motivation, intellectual stimulation and individualized consideration. Respondents of this study were 110 employees in Department of Statistic, Kedah. Data were analyzed using SPSS version 15. The tests conducted were Descriptive analysis, Reliability, Pearson’s Correlation and Multiple regressions. Descriptive analysis was conducted to determine response rate, and the profile of respondents. Additional information such as minimum, maximum, means, range and stadard deviation were also obtained from the analysis. The results from Pearson Correlation Analysis indicate that each dimensions of transformational leadership, namely, idealized influence, inspirational consideration, intellectual stimulation and individual consideration, were significantly related to organizational citizenship behavior. However, taken together, idealized influence is clearly found only was significantly related to OCB based on the regression analysis.